The Teachers Strategy in Teaching Reading Comprehension at SMP Swasta Mardi Wiyata Utama Gunung Bayu - Saragih, Natanael (Bulletin of Science Education, 2023)
The aim of this research was to find the teacher’s strategy in teaching reading comprehension at SMP Mardi Wiyata Utama Gunung Bayu in the academic year 2022/2023. This research used qualitative approach and the research used obseravation, questionnaire, recording, and interview as the method of collecting data. The objective of this research is to know the the English teacher’s strategies in teaching reading. the result of research is the english teacher impementing three strategies in teaching reading. They are scaffolding, and qars, (Question and Answer Relationship). Based on the observation, recording, interview, and the data of questionnaire show that the english teacher implement all the strategies in teaching reading. Moreover, the data from questionnaire revealed that most of the students agree that the english teacher has good ability in teaching reading by using those strategy. Keywords: Teachers Strategy, Reading Comprehension, Teaching Reading